2009
DOI: 10.1016/j.jpubeco.2009.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Tax compliance and firms' strategic interdependence

Abstract: We focus on a relatively neglected area of the tax-compliance literature in economics, the behaviour of firms. We examine the impact of alternative audit rules on receipts from a tax on profits in the context of strategic inter-dependence of firms. In the market firms may compete in terms of either output or price. The enforcement policy can have an effect on firms' behaviour in two dimensions -their market decisions as well as their compliance behaviour. An appropriate design of the enforcement policy can thu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 16 publications
0
42
0
1
Order By: Relevance
“…Bayer and Cowell (2009) have demonstrated that the eectiveness of compliance policy depends on whether there is eective competition or collusion among the rms in the industry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bayer and Cowell (2009) have demonstrated that the eectiveness of compliance policy depends on whether there is eective competition or collusion among the rms in the industry.…”
Section: Introductionmentioning
confidence: 99%
“…By coordinating 3 The result is general and does not depend on either the assumption that there are only two rms or the assumption of linear reaction functions (Bayer and Cowell, 2009). their declarations they can avoid the dilemma that both rms have an incentive to increase their declarations in order to reduce the audit probability.…”
mentioning
confidence: 95%
“…1 Empirical evidence on the performance of audit rules primarily comes from laboratory experiments. 2 The use of field data has proven to be more difficult because of the typical hidden nature of noncompliance and issues of endogeneity of the 1 Compliance behavior of firms has been studied in particular by Crocker and Slemrod (2005), Bayer and Cowell (2009) and Hoopes et al (2012). For extensive reviews of the taxation literature see Andreoni et al (1998), Alm and McKee (1998), Slemrod and Yitzhaki (2002), Slemrod (2007), Kirchler et al (2007) and Alm (2012).…”
Section: Introductionmentioning
confidence: 99%
“…3 We consider a continuum of individuals characterized by their willingness to pay for a good which is subject to a sales tax. Since we focus on the determination of the enforcement level, we assume for most of the paper that the tax rate is set at an exogenous level and we solve the following three-stage model.…”
Section: Introductionmentioning
confidence: 99%